السبل التخطيطية والتصميمية لتحقيق مبادىء االستدامة التقميدية في عمارة اإلسكان المحمية المستقبمية (Journal of Engineering, 2024)
Today, the term "sustainability" became one of the most important concepts of interest in scientific and academic debates. The modern approaches in planning and architecture call for respect of the environment and its ecological system through the harmony among three aspects: economical performance social responsibility and protection behaviors on environment, which is called "sustainable architecture" Obviously, this term can be seen in traditional residential dwellings architecture through the interaction with its local environmental conditions This is what this research deals with by the study and analysis, to determinate the most important principles of traditional house design in terms of climate treatment , building materials choosing and construction methods .In other aspect, the research referred to the existing manners of recent housing architecture .From this analysis and discussion the research explain the wide response of traditional housing to the local environment and exploitation of the natural potentials to the realization of the comfort zone of occupants. Finally, the research tries to indicate the most important planning and design principles to achieve the sustainability in future local housing architecture.